COMPARISON OF SUCCESS OF SLOVENIAN TOP LEVEL ATHLETES AT SENIOR AND JUNIOR COMPETITION LEVEL - Mitija Samardžija Pavletič; Iztok Retar; Poljanka Pavletič Samardžija; Edvard Kolar (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2014)
In this study, we examined whether the Slovenian athletes who are the holders of medals in major competitions in junior categories are among the winners of the most prestigious awards also in senior categories. On a sample of 192 elite sportsmen and sportswomen 98, who during the period from 1 January 2008 to 31 December 2013 achieved the positions from the first to the third place in selected Olympic disciplines in the biggest competitions at junior level competitions and at senior level competitions, we found a result dropout rate of athletes who achieved top results in junior categories after their transition to the senior category. We found that the Slovenian athletes in senior competition level on average achieve top level results at the age of 27. Furthermore, we found out that a half (49 %) of the athletes who achieved excellent results in senior category had not achieved superb results earlier in junior category, and that almost 30 % of athletes who achieved their best results at major competitions on senior levels failed to obtain the status of an athlete of perspective class at the time when they competed in junior category. We have come to the conclusion that unlike the sportsmen achieving top results only a small group of sportswomen achieve top level results. We recommend a systemic analysis of expert professional work in individual sports, adoption of certain measures to improve the competencies of sports managers who coordinate the work of expert teams and the contribution of many other stakeholders who are co-creators of top sports achievements. In addition, we would further suggest the analysis of the categorisation system, particularly in the area of determining the status of perspective athlete. We believe it would be wise to carry out a further in-depth research that would respond to the question who are the key stakeholders and how to influence them in order to reduce the result dropout rate of top young athletes in the transition period to senior categories and to increase the total number of top athletes.